2016
DOI: 10.1007/s10886-016-0793-9
|View full text |Cite
|
Sign up to set email alerts
|

Individual Pheromone Signature in Males: Prerequisite for Pheromone-Mediated Mate Assessment in the Central American Locust, Schistocerca Piceifrons

Abstract: Living in high-density groups of animals has advantages and disadvantages for mating. The advantage of facilitated mate finding is compromised by difficulties in protecting a suitable partner from competitors. Thus, males regularly are faced with increased competition for sperm, and females with harassment by males at high population densities. To cope with these problems, mating tactics and mate choice mechanisms have to be adjusted. An adaptation to gregarious condition observed in locusts includes the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Detailed analyses by Seidelmann et al (2000; and Seidelmann and Ferenz (2002) showed that this substance is released from wings and legs and can be considered a mating regulator or "courtship inhibiting pheromone" as it prevents additional mating between females and other males. In a different species Schistocerca piceifrons, Stahr and Seidelmann (2016) showed that females preferentially mate with males emitting a high concentration of the volatiles phenylethyl alcohol (PEA) and (Z)-3-nonen-1-ol (3-NOL) and this also affected successful hatching of their larvae. Recently, a careful study of Guo et al (2020) identified 4-vinylanisole or 4-methoxystyrene as an aggregation pheromone in Locusta migratoria.…”
Section: Biology Of Phases: Pheromonesmentioning
confidence: 99%
“…Detailed analyses by Seidelmann et al (2000; and Seidelmann and Ferenz (2002) showed that this substance is released from wings and legs and can be considered a mating regulator or "courtship inhibiting pheromone" as it prevents additional mating between females and other males. In a different species Schistocerca piceifrons, Stahr and Seidelmann (2016) showed that females preferentially mate with males emitting a high concentration of the volatiles phenylethyl alcohol (PEA) and (Z)-3-nonen-1-ol (3-NOL) and this also affected successful hatching of their larvae. Recently, a careful study of Guo et al (2020) identified 4-vinylanisole or 4-methoxystyrene as an aggregation pheromone in Locusta migratoria.…”
Section: Biology Of Phases: Pheromonesmentioning
confidence: 99%